The Impact of Aquatic Exercise on Sleep Behaviors in Children with Autism Spectrum Disorder (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Children with Autism Spectrum Disorder (ASD) often demonstrate disturbed sleep behaviors that negatively impact daytime behavior. The purpose of this study was: 1) To determine if participation in aquatic exercise improves sleep duration in children with ASD, and 2) to examine the social validity of the intervention. A within-subjects crossover design over an 8 week period was used. Participants were assigned to the intervention (aquatic exercise 2x/ week for 1 hour) or the control (no exercise) condition for 4 weeks; they then switched conditions for 4 weeks. Sleep habits were recorded using the EMFIT QS sleep monitor. The IRP-15 was administered to parents after completion of the intervention to establish social validity. Mean sleep duration for intervention versus control was compared using the Wilcoxon-Signed Ranks Test. Statistically significant improvements (p=0.012) in sleep duration were observed (intervention:  9.27 hours vs control 8.37 hours). Descriptive statistics were used to analyze IRP-15 data indicating the majority of parents strongly agreed that aquatic exercise had a positive effect on their child’s sleep.Results suggest that participation in an aquatic exercise program may lead to improved sleep duration in children with ASD, and is a socially valid intervention.